Safe and Secure Cities 5th International Conference on Well-Being in the Information Society, WIS 2014, Turku, Finland, August 18-20, 2014. Proceedings - Saranto, Kaija; Castrén, Maaret; Kuusela, Tiina; Hyrynsalmi, Sami; Ojala, Stina (Communications in Computer and Information Science, 2014)
This book constitutes the refereed proceedings of the 5th International Conference on Well-Being in the Information Society, WIS 2014, held in Turku, Finland, in September 2014. The 24 revised full papers presented were carefully reviewed and selected from 64 submissions. The core topic is livability and quality of (urban) living with safety and security. The papers address topics such as secure and equal use of information resources, safe and secure work environments and education institutions, cyberaggression and cybersecurity as well as impact of culture on urban safety and security.